Strength Properties and Uses of Bamboos a Review - Sanyal, S. N.; Gulati, A. S.; Khanduri, A. K. (Indian Forester, 1988)
The basic strength properties evaluated in a systematic way by different workers from time to time are scattered in the form of individual papers and some of the important publications are not readily available. The object of this paper is to compile all the data so far available on physical and mechanical properties of bamboos in different publications in a consolidated form so that it is available for ready reference. An attempt has also been made to analyse the data so collected from different parameters.